MANAGEMENT OF CHRONIC SUPURATIVE OTITIS MEDIA PATIENTS WITH INTRACRANIAL COMPLICATION AT DR. HASAN SADIKIN CENTRAL GENERAL HOSPITAL - Octarian Palmendha, Revy; Mahdiani, Sally; Purwanto, Bambang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Chronic suppurative otitis media (CSOM) is an inflammatory process due to infection of the mucoperiosteum of the middle ear cavity which is characterized by perforation of the tympanic membrane and discharge of secretions. An important problem that arises due to CSOM is intracranial complications that can cause death, so it is necessary to know the characteristics of CSOM patients with intracranial complications. Methods: This study was a retrospective descriptive study on CSOM patients with intracranial complications who were treated at Dr. Hasan Sadikin central general hospital, in the period January 1, 2014 - December 31, 2019. Results: A total of 39 CSOM patients with intracranial complications in the period 1 January 2014 - 31 December 2019. After exclusion, there were 33 total samples in this study. The group after the most was 18-34 years and it was more common in men. The chief complaint from the most patients was headache and as many as 30 people did not have comorbid diseases, and as many as 15 people experienced complications of subdural abscess. Conclusion: From the results of this study it was concluded that there were significant differences based on gender, age, and educational background. The most common complaint of patients was headache, without comorbidities, and the most common complication was subdural abscess, and the duration of time from otitis media to intracranial complications was >5 years.